IPv6 Addressing and Configuration: Building a Dual-Stack Network with OSPFv3 - ALGAZITE, Hussam EDDIN; Nuredin Ahmed (AlQalam Journal of Medical and Applied Sciences, 2025)
With the rapid growth of Internet-connected devices, IPv4 addressing has become insufficient to meet global demand. IPv6 was introduced to overcome this limitation by providing a significantly larger address space and improved routing efficiency. This project focuses on designing and implementing a dual-stack network that supports both IPv4 and IPv6. The network primarily operates using IPv6 while maintaining compatibility with IPv4 through a controlled and realistic transition model. The implementation includes IPv6 Global Unicast Addressing (GUA), Link-Local Address configuration, dynamic routing using OSPFv3, static routing for IPv4, and end-to-end connectivity testing using IPv6 ping and traceroute. The project successfully demonstrates the deployment of an IPv6-based network with seamless IPv4 integration, reflecting real-world enterprise transition scenarios.